اأثر أدارة المعرفة في التعلم التنظيمي بالجامعات الليبية - Mohamed M.M. Ensair (Universiti Sains Islam Malaysia, 2024)
Over the last two decades,the world has witnessed the emergence of influential forces that have reshaped both economic and administrative systems.These forces have included globalisation,the liberalisation of trade,the economy,new technology and the need and ability for organisations to promptly adapt and respond to these changes.Subsequently,this has prompted,if not driven organisations to seek and acquire new knowledge and organisational learning to improve their competitiveness.Undoubtedly, this will help to increase their knowledge base,the ability to manage information and support decision-makers in shaping future policies and plans to achieve optimal performance.Accordingly,this study aims to analyse the validity of knowledge management infrastructure standards,the knowledge management process and organisational learning in oder to determine if the model fits the data. The study further aims to analyse the direct and indirect relationships between the various elements associated with infrastructure, processes and organisational learning in respect to knowledge management followed by analysing gender,degree and experience variables.In achieving the aim and objectives of this study,the researcher adopted a quantitative approach by employing a survey method in order to discover the causal relations between knowledge management and organisational learning,specifically in Libyan universities.IBM’s SPSS statistics program (Statistical Package for the Social Sciences) was used along with structural equation modelling (SEM) using the AMOS program as it offers the researcher the ability to test the relations between all variables simultaneously. To achieve the appropriate sample size,the researcher distributed 600 questionnaires,of which 503 were returned (retrieval rate of 83%).The results of the study indicated that the scales associated knowledge management infrastructure,the knowledge management process and organisational learning matched the sample data.Furthermore,the SEM results revealed that the direct relationships between the three were positively and statistically significant.Moreover,the knowledge management process as a mediator variable was shown to be positive and significant.However,a difference was observed between gender degree and experience in the proposed model.Notably,the most important contribution of the study was study was the emphasis on the complementary relationship between knowledge management and organisational learning,as reflected in the relevant theories.The main recommendations of the study propose that senior management should prioritise knowledge management (KM) and organisational learning (OL),along with the provision of all essential inputs,which contribute towards the generation,tranfer and application of knowledge.